Effect of changes in food price on the quinoa consumption and rural food security in Peru (Scientia Agropecuaria, 2020)
The objective of this study was to determine the effect of changes in prices on food consumption of rural producers in Junin (Peru) in order to verify if there are some differences in food security between farmers who produce quinoa and those who do not. For this purpose, surveys were applied to 277 producers and the data from the National Household Survey (2016) were used to assess the dimensions of food security. It was found that local food has lower elasticity values than foreign one, but the variability of local food prices is higher. In addition, 27.3% of the population does not satisfy the caloric requirements, and that the quinoa consumption is associated with its nutritional value and cultural factors. In Junin’s rural population a low nutritional value consumption is evident, and there are not significant differences in the daily food consumption between producers who farm the quinoa and those who do not. Therefore, food price increases would equally impact both producer groups.
Keywords: Demand elasticity; food security; food customs; Tobit model; quinoa.